Applications of indocyanine green (ICG) fluorescence technology in open surgery: preliminary experience in pediatric surgery - Esposito, Ciro; Lepore, Benedetta; Cerulo, Mariapina; Del Conte, Fulvia; Coppola, Vincenzo; Esposito, Giovanni; Carulli, Roberto; Carraturo, Francesca; Escolino, Maria (Frontiers in Surgery, 2023)
Background: Indocyanine green fluorescence technology (ICG) in pediatric minimally invasive surgery has undergone an important improvement in the last 5 years. However, its use in open surgery is still limited. In this paper, we aim to report our preliminary experience with Rubina® lens ICG fluorescence technology in combination with the IMAGE1 S™ system from KARL STORZ in open excision of masses in children.The records of 18 patients undergoing open surgery for head, neck and thorax masses between September and November 2022 were retrospectively reviewed. Rubina ® lens ICG fluorescence technology system was used in all the cases. In 10 cases we adopted the holding arm system and in 8 cases the hand-held technique. Data about patients' demographics, surgery and outcomes were collected and analyzed through the following criteria: mass localization, intraoperative time (min), ICG administration (ml), intraoperative complications, postoperative complications.Results: A total of 18 patients were operated: 4 thyroglossal duct cysts, 3 supraorbital cysts, 2 neck masses, 2 pre-auricular and 2 scalp cysts, 2 gynecomastias, 2 lymphangiomas, 1 nose mass. In all the cases, intralesional injection of 0.5-1ml of ICG solution was performed peri-operatively. Mean operative time was 58.4 min (35-134 min). Postoperative complications included seroma formation in 2 cases. Surgical pathology reports confirmed complete mass excision in all the cases.Based on our preliminary experience, ICG fluorescence guided surgery using Rubina® lens system was very helpful also in open surgery procedures. Rubina® lens system permits to have a very low complication rate, a time-saving surgery, a real time reliability of anatomic structures and an excellent clinical safety. In our experience, holding arm system seems more comfortable than hand-held system. However, further cases need to be performed to evaluate the exact role and to identify new indications of this technique in open pediatric surgical procedures.